Sources of practice knowledge among nurses - Estabrooks, Carole; Rutakumwa, William; O’Leary, Katherine; Profetto McGrath, Joanne; Milner, Margaret; Levers, Merry Jo; Scott Findlay, Shannon (My University, 2005)
Several studies have been published listing sources of practice knowledge used by nurses. However, the authors located no studies that asked clinicians to describe comprehensively and categorize the kinds of knowledge needed to practice or in which the researchers attempted to understand how clinicians privilege various knowledge sources. In this article, the authors report findings from two large ethnographic case studies in which sources of practice knowledge was a subsidiary theme. They draw on data from individual and card sort interviews, as well as participant observations, to identify nurses’ sources of practice knowledge. Their findings demonstrate that nurses categorize their sources of practice knowledge into four broad groupings: social interactions, experiential knowledge, documents, and a priori knowledge. The insights gained add new understanding about sources of knowledge used by nurses and challenge the disproportionate weight that proponents of the evidence-based movement ascribe to research knowledge.
Keywords: sources of knowledge; research utilization; case study; ethnography; ethnoscience